1990
DOI: 10.1210/jcem-71-4-1051
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Thyrotropin Binding-Inhibiting Immunoglobulins and Thyroid-Stimulating Antibodies in Patients with Silent Thyroiditis

Abstract: Silent (painless) thyroiditis has been recognized as a clinical entity for over a decade and is characterized by spontaneously resolving thyrotoxicosis. Its etiology is uncertain; however, a few reports have indicated the occurrence of TSH binding-inhibiting immunoglobulins (TBII) and thyroid-stimulating antibodies (TSAb) in some of the patients. The present study was undertaken to evaluate thyroid function and the occurrence of TBII and TSAb and thyroid autoantibodies (antithyroglobulin and antimicrosomal) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
2
7

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 29 publications
3
38
2
7
Order By: Relevance
“…TBII is positive in patients with Graves' disease in 80-90%, but it is also positive in patients with silent thyroiditis in about 15% [12]. Treatment with antithyroid drugs for silent thyroiditis is inappropriate.…”
mentioning
confidence: 99%
“…TBII is positive in patients with Graves' disease in 80-90%, but it is also positive in patients with silent thyroiditis in about 15% [12]. Treatment with antithyroid drugs for silent thyroiditis is inappropriate.…”
mentioning
confidence: 99%
“…Morita et al (18 ) reported that increased levels of TBIIs and TSAb may be detected in patients with silent thyroiditis who developed transient hypothyroidism during the course of the disease. They mentioned that TBIIs and TSAb were related to the thyroid damage that caused transient hypothyroidism occurring during the course of silent thyroiditis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Morita et al (18 ) reported that increased levels of TBIIs and TSAb may be detected in patients with silent thyroiditis who developed transient hypothyroidism during the course of the disease. They mentioned that TBIIs and TSAb were related to the thyroid damage that caused transient hypothyroidism occurring during the course of silent thyroiditis (18). Momotani et al (16) reported that serum levels of TBIIs increased and then decreased in the majority of the patients with postpartum thyrotoxicosis irrespective of the courses of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[21]. Cases with the co-existence of TSAb and TSBAb [22] and cases in which TSAb activity changed to TSBAb activity after radioisotope treatment in Graves' disease have been reported [23]. These lines of evidence suggest that the biological activity of patient's IgG depends on the differences in amount of TSAb and TSBAb, so that TBII and TS activities in the co-existence of TSAb and TSBAb may be expressed by the following formula.…”
Section: Latsmentioning
confidence: 99%